Operationalizing respectful maternity care at the healthcare provider level: a systematic scoping review - R. Rima Jolivet; Jewel Gausman; Neena Kapoor; Ana Langer; Jigyasa Sharma; Katherine E. A. Semrau (BMC, 2021)
Plain Language Summary Respectful care for mothers and newborns is a right and important part of ensuring that their care is high quality and acceptable to them. Just because there is no mistreatment does not mean that Respectful Maternity Care (RMC) was given. Without a clear framework for provider behaviors that reflect RMC principles, it is hard to ensure every woman and newborn gets respectful care in practice. We compared and combined two frameworks summarizing maternal and newborn rights and came out with seven categories. Then we searched for articles that mentioned provider behaviors reflecting RMC. We found 514 articles and ended up with 54 after careful review, from which we pulled the observable behaviors for providers in each category. Almost all papers mentioned actions to protect women and newborns from harm and mistreatment, to treat them with dignity and respect, and to give information and respect choices. About half of papers mentioned actions to protect privacy and to make sure every mother and newborn gets care when needed. Only 25% of papers mentioned actions to make sure all women and newborns receive equal care, and only 15% included actions to make sure women and newborns are physically free to leave facilities at will, and get care whether or not they can pay. This framework defining RMC behaviors for providers is based on data from many studies and can be useful to look at whether maternal newborn care in facilities meets these standards and to inform training and more research to improve RMC.